PENGARUH KETERSEDIAAN TEMPAT, PERPUTARAN BARANG DAN ALUR KERJA PADA PROSES PRODUKSI PADA INDUSTRI MANUFAKTURING TERHADAP EKSPANSI PERUSAHAAN - Kartika Sari Dewi; Sri Lestari (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
The aim of this research is to recognize and analyze how limited space can affect the turnover of goods in the production process in a manufacturing company. This research was created for quantitative testing because the methodology used to be recommended by researchers is based on process, speculation, going into the field, testing information, and preparation using parts of estimation, calculation, equations and certainty of mathematical information. The subjects of this research are company employees. Information was examined using a variety of direct relapse prescriptions and speculative testing. The test results show that the Fstatistic figure of 1.36 is more significant than the Ftable figure of 2.51 and the requirement figure of 0.93 is based on 0.05. This proves that the after effects review refutes H0. So that the Production Process Flow (X1), Goods Turnover Flow (X2), Goods Availability (X3) and Warehouse Capacity (Y) have an important influence on the company's expansion.